On the Best Polynomial Approximations of 2π-Periodic Functions and Exact Values of n-Widths of Functional Classes in the Space L_2 - Vakarchuk, S. B. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
To solve extremal problems of approximation theory in the space L_2, we use τ-moduli introduced by Ivanov. We determine the exact values of constants in Jackson-type inequalities and the exact values of n-widths of functional classes determined by these moduli.